2017
DOI: 10.14254/1800-5845/2017.13-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Multidimensional View of Intellectual Capital and Business Ethics on Organizational Performance by Using Bootstrapping Method: Evidence from Pakistani Pharmaceutical Industry

Abstract: The objective of this research is to examine the effect of business ethics (BE) and intellectual capital (IC) on the organizational performance (OP). In order to run this study, a conceptual model was designed based on the literature review, and the employees of the knowledge-based organization in pharmaceutical sector were surveyed using a closed-ended questionnaire. Modern successful and thriving organizations are those that create IC and convert it into applicable methods to improve their activities and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 82 publications
0
8
0
2
Order By: Relevance
“…According to Anderson & Gerbing (1988), the collected data should follow the normality pattern, and it is a prerequisite for structural equation modelling and other SEM based multivariate statistical techniques. Thus, we converted all the responses into Z score, and the results of descriptive statistics showed that kurtosis values lay between ±3, and skewness and standard deviation values were in the rage of ±1.5, thus, this further proved that our data was following the normality pattern (Ahmed et al, 2017).…”
Section: Descriptive Statisticsmentioning
confidence: 78%
See 4 more Smart Citations
“…According to Anderson & Gerbing (1988), the collected data should follow the normality pattern, and it is a prerequisite for structural equation modelling and other SEM based multivariate statistical techniques. Thus, we converted all the responses into Z score, and the results of descriptive statistics showed that kurtosis values lay between ±3, and skewness and standard deviation values were in the rage of ±1.5, thus, this further proved that our data was following the normality pattern (Ahmed et al, 2017).…”
Section: Descriptive Statisticsmentioning
confidence: 78%
“…The values of Cronbach's Alpha and composite reliabilities, which are over 0.65 and just approach 0.70 for all the factors, showed that the reliabilities meet the minimum criterion of threshold, i.e., 0.60. Moreover, the results of factor loading for all constructs range between 0.50-0.85, satisfying the minimum criteria of discriminant validity (Ahmed et al, 2017). Further, the values of the average variance extracted (AVE) are more than 0.50, thus, a condition of convergent validity is also satisfied (Fornell & Larcker, 1981).…”
Section: Reliabilities and Ave Analysismentioning
confidence: 86%
See 3 more Smart Citations